Assessment of genetically modified soybean MON 87705 × MON 87708 × MON 89788, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2015‐126). (18th May 2020) - ; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Soybean MON 87705 × MON 87708 × MON 89788 (three‐event stack soybean) was produced by conventional crossing to combine three single soybean events: MON 87705, MON 87708 and MON 89788. This combination is intended to alter the fatty acid profile in the seed (in particular increasing the levels of oleic acid) and tolerance to glyphosate‐based and dicamba herbicides. The Genetically Modified Organisms Panel previously assessed the three single soybean events and did not identify safety concerns. No new data on the single soybean events, leading to modification of the original conclusions on their safety have been identified. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single soybean events and of the newly expressed proteins in the three‐event stack soybean does not give rise to food and feed safety and nutritional concerns. In the case of accidental release of viable three‐event stack soybean seeds into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and the reporting intervals are in line with the intended uses of soybean MON 87705 × MON 87708 × MON 89788. Considering the altered fatty acid profile of the three‐event stack soybean, a proposal for post‐market monitoring needs to be provided by the applicant. The GMO Panel notes that in the context of this application EFSA‐GMO‐NL‐2015‐126 the applicant did not provide a 90‐day study on MON 87705 soybean in line with the applicable legal requirements. Therefore, the GMO Panel is not in the position to finalise the risk assessment of soybean MON 87705 × MON 87708 × MON 89788 under the current regulatory frame.